Enhancing the understanding of safety and the quality of patient care among medical and health sciences students in interprofessional climate: an interventional study - Salman Yousuf Guraya; Nabil Sulaiman; Ahmed Hasswan; Vida Abdolhamid Salmanpour; Feras Jassim Jirjees; Mohamed Hassan Taha; Jennat Alamara; Sausan A.L. Kawas; Manal Awad; Jacqueline Maria Dias; Leena R. David; Mohamed Aly Haider; et al. (BMC Health Services Research)
Abstract Background Interprofessional education (IPE) plays an essential role in improving healthcare outcomes through achieving shared understanding. Unfortunately, most healthcare professionals have not received training for patient safety (PS) in an interprofessional setting, which can meet the societal medical needs. This study aimed to foster the understanding of senior medical, dental, pharmacy and health sciences students about PS and quality of care at the University of Sharjah (UoS) in UAE. Methods Using a convenience sampling technique, we recruited students from the College of Medicine (CoM), College of Pharmacy (CoP), College of Dental Medicine (CDM), and College of Health Sciences (CHS) of UoS. The study was conducted in spring 2023, and an ethical approval was obtained from the UoS Research Ethics Committee (REC-21–12-12). After a thorough literature search, a bespoke English language questionnaire was developed covering three domains—medical professionalism, leadership in healthcare, and precision medicine. To ensure its validity across different settings, cultural adaptation was ensured with reiterative revision among the panel of experts. The online synchronous real-time workshop included interactive resource sessions, breakout room discussions using real clinical cases, and pre-post surveys using the questionnaire. Results A total of 248 students and 20 facilitators participated in the workshop. CoM had the highest representation (47.5%), followed by CoP (36.5%), CHS (13.3%), and CDM (2.7%). There was a statistically improved understanding of the participants, as reflected by significantly high scores of post-test survey in all domains of PS across all colleges (p < 0.001). Notably, students in years four and five from CoM and CoP showed significant improvement in their perceptions than other colleges (p < 0.001). The participants encountered challenges of weak internet connections, software issues, technical failures, and power outages during the workshop. Conclusion This study highlights the positive impact of an IPE-based interventional workshop on students' attitudes, perceptions, and insights about PS and quality of care. Students' understanding and insights of PS and quality of care underscore the paramount role of IPE in improving perceptions and approaches towards PS in the context of healthcare education.